The Biosafety and Risk Management in Preparation and Processing of Cerebrospinal Fluid and Other Neurological Specimens With Potential Coronavirus Infection - Chen, Chien-Chin; Chiang, Pei-Chun; Chen, Tsung-Hsien (Frontiers in Neurology, 2021)
The recent outbreak of coronavirus disease 2019 (COVID-19), caused by Severe Acute Respiratory Syndrome Coronavirus 2, has become a global threat. Due to neurological manifestations presented throughout the coronavirus disease process, the potential involvement of COVID-19 in central nervous system has attracted considerable attention. Notably, the neurologic system could be widely affected, with various complications such as acute cerebrovascular events, encephalitis, Guillain-Barré syndrome, and acute necrotizing hemorrhagic encephalopathy. However, the risk assessment of exposure to potential biohazards in the context of the COVID-19 pandemic has not been clearly clarified regarding the sampling, preparation, and processing neurological specimens. Further risk managements and implantations are seldom discussed either. This article aims to provide current recommendations and evidence-based reviews on biosafety issues of preparation and processing of cerebrospinal fluid and neurological specimens with potential coronavirus infection from the bedside to the laboratory.